Pricing Electric Power under a Hybrid Wholesale Mechanism: Evaluating the Turkish Electricity Market - Karahan, Hatice; Toptas, Mehmet (International Journal of Energy Economics and Policy, 2013)
<!--[if gte mso 9]> Normal 0 false false false TR X-NONE X-NONE <![endif]--> During the restructuring process, Turkish electricity sector has gone through significant changes both in wholesale and retail markets. In this framework, the Market Financial Settlement Mechanism established for handling market imbalances has become a spot market in time. So, it can be claimed that the wholesale electricity market in Turkey is a hybrid mechanism composed of bilateral contracts and the balancing market. On the other hand, the main target of liberalization program is providing consumers with affordable electric power. Hence, this study attempts to explore the link between retail tariffs for ineligible consumers and prices in the two wholesale mechanisms, in the period after the launch of the day-ahead market. Findings suggest that regulated wholesale prices are more effective in the determination of end-user prices, whereas unregulated ones might have a price reduction effect in case the free market dominates. However, the volatility in spot market prices implies that the sector would better continue with the hybrid mechanism for quite some time. Keywords: Electricity Prices; Wholesale; Retail; Competition; Turkey JEL Classifications: D40; Q40; Q43 <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->